Conflicting patterns of thought in the Russian debate on transition: 2003-2007 - Joachim Zweynert (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2009)
This article is a continuation of two essays by the same author on Soviet/Russian economic debates between 1987 and 2002 published in Europe-Asia Studies in 2006 and 2007, so now the series of articles covers 20 years of Soviet/Russian discussions on economic reforms. Should Russia strive to become a 'Western' country marked by democracy and a market economy serving the individual interests of its citizens, or was it more important to become a great power again? Are Western patterns of political and economic life suitable for Russia or is the attempt to import foreign institutional structures doomed for failure, making it necessary for Russia to find her own way? This type of question, going far beyond the realm of economics, was and still is at the heart of the debate among Russian economists, which shall be discussed here, on the basis of a qualitative content analysis of the most important economic journals and selected monographs.
Keywords: 330